212k views
2 votes
Which expression is equal to (f - g)(x)?

Which expression is equal to (f - g)(x)?-example-1
User Shangxinbo
by
5.7k points

2 Answers

7 votes

The correct option is c.


$7 x^2+2 x+13$ is equal to
$(f-g)(x)$.

To find the expression for
\((f-g)(x)\), we need to subtract the function
\(g(x)\) from
\(f(x)\). Let's do this step by step.

The functions
\(f(x)\) and
\(g(x)\) are given as:


\[ f(x) = 7x^2 + 4 \]


\[ g(x) = 2x + 9 \]

Now,
\((f-g)(x)\) is defined as:


\[ (f-g)(x) = f(x) - g(x) \]

Substituting the given functions into this, we get:


\[ (f-g)(x) = (7x^2 + 4) - (2x + 9) \]

Now, let's simplify this expression:


\[ (f-g)(x) = 7x^2 + 4 - 2x - 9 \]

To simplify the expression
\((f-g)(x) = 7x^2 + 4 - 2x - 9\), you can simply subtract
\(g(x)\) from
\(f(x)\):


\[(f-g)(x) = f(x) - g(x) = (7x^2 + 4) - (-2x - 9)\]

Now, you can simplify further by distributing the negative sign on
\(-(-2x - 9)\) to make it positive:


\[(f-g)(x) = 7x^2 + 4 + (2x + 9)\]

Now, combine like terms:


\[(f-g)(x) = 7x^2 + 2x + 13\]

So,
\((f-g)(x) = 7x^2 + 2x + 13\).

Therefore, the answer is
$7 x^2+2 x+13$.

User Nayrb
by
5.2k points
4 votes

Answer: Option D


(f-g)(x) = 7x^2 -2x -5

Explanation:

We have two functions:


f (x) = 7x ^ 2 +4\\\\g (x) = 2x + 9

We must find (f-g)(x)

Then we must subtract the function f and the function g.

Therefore we have that:


(f-g) (x) = f (x) -g (x)\\\\(f-g) (x) = 7x ^ 2 +4 - (2x + 9)\\\\(f-g) (x) = 7x ^ 2 -2x -5

Therefore the correct option is the last option (Option D)
(f-g)(x) = 7x^2 -2x -5

User Joey Yi Zhao
by
6.2k points